Can God create humans with free will who never commit evil? - Thai, Lee Pham (HTS teologiese studies, 2020)
Can an omnipotent and omnibenevolent God create humans with free will without the capacity to commit evil? Scholars have taken opposite positions on the contentious problem. Using scripture and the rules of logic, we argue that God cannot create impeccable creatures because of his ‘simplicity’. God cannot create gods, because God is uncreated. Peccable humans freely choose to disobey their creator and thus cannot blame him for the horrendous evils in this world. Concerning the belief of sinless humans with free will in heaven, we suggest that such an impartation of God’s impeccability can be accomplished, not through creation, but by the marriage of Christ and the Church, for the two shall become one. Believers will become children of God and partakers of the divine nature.Contribution: Theologians and philosophers have argued whether God could create humans with free will who never commit evil, and if he could, why did he not do so? The primary contribution of this article is the argument that God could not create impeccable humans with free will for God could not create gods.